Nanoparticle-electrode collision processes: The electroplating of bulk cadmium on impacting silver nanoparticles - Zhou, Y; Rees, N; Compton, R (2011)
We report, for the first time, the bulk deposition (electroplating) of a metal onto nanoparticles during collisions with an inert electrode surface. Experiments show that for silver nanoparticles, multiple layers of Cd atoms can be electroplated onto the AgNPs from aqueous Cd2+ during collisions with a glassy carbon electrode held at a suitably reducing potential, and an average of 19 atomic layers of cadmium are found to be deposited in the few milliseconds that the NP is in contact with the electrode. For comparison, results are also presented for the underpotential deposition of Cd onto AgNPs under similar conditions. © 2011 Elsevier B.V. All rights reserved.